Acetylxylan‐pheophorbide‐a nanoparticles designed for tumor‐targeted photodynamic therapy. Issue 32 (2nd April 2021) - Bouramtane, Soukaina; Bretin, Ludovic; Pinon, Aline; Leger, David; Liagre, Bertrand; Perez, Denilson Da Silva; Launay, Yann; Brégier, Frédérique; Sol, Vincent; Chaleix, Vincent
Abstract: The poor solubility of most photosensitizers (PS) hampers their practical use as clinical agents. Conjugation of PS with water‐soluble nanoparticles has been often used to bypass this hurdle. We describe in this study the extraction of glucuronoacetylxylan from chestnut sawdust, the hemisynthesis of pheophorbide‐a (Pha) and its covalent attachment to xylan. The resulting conjugates (xyl‐Pha) spontaneously form water‐soluble spherical nanoparticles (xyl‐Pha NPs) ranging between 100 and 250 nm in diameter. Assayed against the HT‐29 colorectal cancer cell line, xyl‐Pha NPs exhibited a dose‐dependent phototoxicity only when irradiated with red light. Abstract : Acetylated glucuronoxylan extracted from chestnut sawdust and functionalized with Pheophorbide‐a obtained by hemisynthesis from spirulina spontaneously forms spherical nanoparticles with diameters between 100 and 250 nm, and these new biosourced photosensitive nanoparticles, which are non‐toxic in the dark, exhibited dose‐dependent phototoxicity against the HT‐29 colorectal cancer cell line only when irradiated with red light.